Anaerobic digestion of cheese whey: Energetic and nutritional potential for the dairy sector in developing countries. (January 2018) - Escalante, H.; Castro, L.; Amaya, M.P.; Jaimes, L.; Jaimes-Estévez, J.
Graphical abstract: Highlights: This research presents a full characterization of cheese whey (CW) from 4 companies. This work identified opportunities to recover energy and nutrients from CW. Nutritional content in CW digestate is adequate to precipitate struvite. We present anaerobic digestion as a two-way street between dairy companies and farms. Abstract: Cheese whey (CW) is the main waste generated in the cheesemaking process and has high organic matter content and acidity. Therefore, CW disposal is a challenge for small to medium enterprises (SMEs) in the dairy industry that do not have any type of treatment plant. Anaerobic digestion (AD) is an attractive process for solving this problem. The aim of this research was to determine the biomethane and struvite precipitation potentials of CW from four dairy SMEs. First, changes in CW properties (organic matter and pH) were evaluated. Second, biomethane and struvite potentials were assessed using cattle slurry as inoculum. The organic matter in CW varied from 40 to 65 g VS/kg, 65 to 140 g COD/L, and 2 to 10 g/L for VFAs depending on the sampling time and type of sample. The pH of the CW samples ranged from 3 to 6.5. In the anaerobic biodegradability analysis, methane yields reached 0.51 to 0.60 L CH4 /g VSadded, which represented electrical and caloric potentials of 54 and 108 kW h/m 3 for CW, respectively. Organic matter removal in all experiments was above 83%. Moreover, anaerobic digestates presented NH4 + /PO4 3− molar ratios between 2.6 and 4.0, which are adequate for struvite precipitation with potential production of 8.5–10.4 g struvite/L CW. Finally, the use of biogas as energetic supplement and struvite as soil fertilizer, represents economics saves of US 6.91/m 3 CW and US 5.75/m 3 CW in therms of electricity and fertilizer use, respectively. The energetic, agricultural and economic potentials, evidence that AD process is a feasible alternative for cheese whey treatment.